Is Activity-Resource-based View (ARBV) the New Theory of the Firm for Creating Sources of Sustainable Competitive Advantage in Services Firms? (Global Journal of Management and Business Research, 2016)
This paper advocates the extension of the resource based view (RBV) by proposing a new theory to understand the actual creation process of sustainable competitive advantage using a services firm in the motor industry in Kenya as a case, by integrating the activity-based view (ABV) with the RBV, through activity drivers, to generate a new theory: Activity-resourcebased view (ARBV). A qualitative case study of a consistently high performing firm in the motor services industry in Kenya was used to determine if the ARBV assists in creating a sustainable competitive advantage. The results from the in depth semi-structured qualitative case study shows that a firm in a motor service industry that adopts the new theory, ARBV, will generate and sustain a competitive advantage for itself.
Keywords: activity-resource based view; activity drivers; and sustainable competitive advantage; activity and resource-based view; sustainable competitive advan